2012
DOI: 10.1186/1471-2458-12-629
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance patterns and decision-making for human papillomavirus vaccination among parents in Vietnam: an in-depth qualitative study post-vaccination

Abstract: BackgroundThe GAVI Alliance’s decision in late 2011 to invite developing countries to apply for funding for human papillomavirus (HPV) vaccine introduction underscores the importance of understanding levels of HPV vaccine acceptance in developing country settings. In this paper, we present findings from qualitative research on parents’ rationales for vaccinating or not vaccinating their daughters (vaccine acceptance) and their decision-making process in the context of an HPV vaccination demonstration project i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 30 publications
5
34
0
6
Order By: Relevance
“…A study determined a low acceptability of HPV vaccinations among parents of adolescents in China. Cover et al (2012) demonstrated that parents who did not allow their children to be vaccinated were concerned about the involved vaccine's side effects, the possibility that the vaccine was experimental, and the impact of the vaccine on future fertility. To educate parents and improve vaccination rates.…”
Section: Hpv Vaccine Knowledge and Perceived Risk Of Cervical Cancer mentioning
confidence: 99%
“…A study determined a low acceptability of HPV vaccinations among parents of adolescents in China. Cover et al (2012) demonstrated that parents who did not allow their children to be vaccinated were concerned about the involved vaccine's side effects, the possibility that the vaccine was experimental, and the impact of the vaccine on future fertility. To educate parents and improve vaccination rates.…”
Section: Hpv Vaccine Knowledge and Perceived Risk Of Cervical Cancer mentioning
confidence: 99%
“…[11][12][13][14][15][16][17] For school-based outreach, vaccine coverage was 82.6% in Peru, 88.9% in Uganda and Objective To estimate the incremental delivery cost of human papillomavirus (HPV) vaccination of young adolescent girls in Peru, Uganda and Viet Nam. Methods Data were collected from a sample of facilities that participated in five demonstration projects for HPV vaccine delivery: schoolbased delivery was used in Peru, Uganda and Viet Nam; health-centre-based delivery was also used in Viet Nam; and integrated delivery, which involved existing health services, was also used in Uganda.…”
Section: Introductionmentioning
confidence: 99%
“…Given the fact that vaccinating pre-adolescents and adolescents is a relatively new phenomenon in many resource-limited settings, formative socio-behavioral research is essential for providing a framework for optimizing vaccine uptake. Qualitative research in Peru [26], India [27], Uganda [28], and Vietnam [29], [30], illustrate the need to understand psychosocial barriers to HPV vaccination, including concerns about vaccine safety and efficacy, and its impact on future fertility in order to effectively design programs that would optimize vaccine uptake [31].…”
Section: Introductionmentioning
confidence: 99%